2019
DOI: 10.1021/acs.jnatprod.9b00224
|View full text |Cite
|
Sign up to set email alerts
|

Constituents of the Edible Leaves of Melicope pteleifolia with Potential Analgesic Activity

Abstract: Melicope pteleifolia has long been consumed as a popular vegetable and tea in Southeast Asian countries, including Malaysia and southern mainland China, and is effective in the treatment of colds and inflammation. In the search for active metabolites that can explain its traditional use as an antipyretic, six new phloroacetophenone derivatives (3−8) along with seven known compounds (1, 2, and 9−13) were isolated from the leaves of M. pteleifolia. Their chemical structures were confirmed by extensive spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Moreover, our previous studies on M. pteleifolia have demonstrated that the phloroacetophenone derivatives dominantly present in the plant play an important role in recovery from cold by lowering excessive heat in the animal model, by which we proved scientifically ethnopharmacological uses of the plant …”
Section: Introductionmentioning
confidence: 88%
“…Moreover, our previous studies on M. pteleifolia have demonstrated that the phloroacetophenone derivatives dominantly present in the plant play an important role in recovery from cold by lowering excessive heat in the animal model, by which we proved scientifically ethnopharmacological uses of the plant …”
Section: Introductionmentioning
confidence: 88%
“…Phenyl C -glycosides were considered the simplest aryl- C -glycosides. The disclosed structures 140 – 169 feature C - β -D-glucopyranosides, with variations in the substitution on the benzene ring ( Figure 5 ) [ 24 , 25 , 26 , 27 , 80 , 81 , 82 , 83 , 84 ]. The site of C -glycosylation is usually the ortho position of the phenolic hydroxyl group.…”
Section: Structuresmentioning
confidence: 99%
“…Ardimerin digallate ( 169 ) was isolated from the whole plant of Ardisia japonica and was shown to inhibit HIV-1 and HIV-2 RNase H in vitro, with IC 50 values of 1.5 and 1.1 µM, respectively [ 27 ]. The compound 3,5-di- C - β -D-glucopyranosyl phloroacetophenone ( 155 ), isolated from the edible leaves of Melicope pteleifolia , was found to be responsible for the antipyretic activity of M. pteleifolia based on in vivo experiments [ 26 ]. Calophymembranside C ( 141 ), isolated from the stems of Calophyllum membranaceum , showed transcriptional inhibitory activity towards RXRα, with 50% inhibitory concentration (IC 50 ) values of 29.95 ± 1.08 [ 24 ].…”
Section: Pharmacological Activitymentioning
confidence: 99%
“…Folkloric uses of plants against different diseases act as a pivot to explore those plants for new bioactive compounds and affirmative activities of crude plant extracts usher identification and isolation of many compounds. For instance, in recent years, several compounds from plant sources have been reported to possess antinociceptive (Mizokami et al, 2012;Nieto et al, 2013;Sun et al, 2019) and antipyretic effect (Lee et al, 2019;Muhammad et al, 2019). A good number of plants native to Bangladesh have been traditionally used against pain and fever and their effects are underpinned by experimental findings in animal model (Ferdous et al, 2020;Roy et al, 2019;Subedi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%